“Police took my homie I dedicate my life 2 his revenge”: Twitter tensions between gang-involved youth and police in Chicago. - Patton, Desmond Upton; Leonard, Patrick; Cahill, Loren; Macbeth, Jamie; Crosby, Shantel; Brunton, Douglas-Wade (Journal of Human Behavior in the Social Environment)
The hostile and adversarial relationship between youth and police in urban settings has remained pervasive and persistent for centuries. This is a tension historically rooted in the miasma of lack of trust; racial, ethnic, and cultural differences; and fear, anger, and hostility from racialized surveillance and policing. Indeed, most Black youth have little contact with police unless it involves harsh profiling and/or criminalization. In this article, we leverage the policing literature to examine how the perpetual detestation between urban youth and police is expressed in physical and digital contexts (e.g., Twitter). We find that urban youth, particularly gang-involved youth, publicly articulate their disdain for law enforcement agents on Twitter. The young people in our study expressed chronic grief and anger after the fatal police shooting of a Southside Chicago gang member. Further, they expressed a strong desire to violently retaliate against the Chicago Police Department after their friend was killed. In fact, users on Twitter frequently posted the hash tag #CPDK—an acronym for Chicago Police Department Killer—shortly after this incident. We discuss the implications of using Twitter data to inform policing practices, as well as early intervention and prevention strategies for youth living in inner cities.